Role of thyroid autoimmunity independent of thyroid hormone levels in pulmonary function decline: A population-based study in euthyroid adults - Kyung-Hun Sung; Jeongeun Kwak; Mee Kyung Kim; Dong-Jun Lim; Jung-Min Lee; Sang-Ah Chang; Jeongmin Lee (PLoS ONE, 2025)
Purpose Although overt thyroid dysfunction has been associated with changes in pulmonary function, the effects of thyroid hormone levels and thyroid autoimmunity on lung function in euthyroid individuals remain unclear. We investigated the associations between subtle changes in thyroid hormones and thyroid peroxidase antibodies (TPOAb) and pulmonary function in a nationally representative cohort of Korean adults. Methods We analyzed data from 2,626 euthyroid participants aged ≥ 40 years from the Korea National Health and Nutrition Examination Survey (2013–2015). Pulmonary function was assessed using spirometry-derived forced vital capacity (FVC), forced expiratory volume in 1 second (FEV1), and FEV1/FVC ratio. Multivariable linear regression analyses were conducted after adjusting for age, sex, body mass index (BMI), smoking status, alcohol intake, and physical activity. Results In the unadjusted models, higher free thyroxine levels were positively associated with FVC and FEV1, while higher TSH levels were inversely associated. In contrast, elevated TPOAb levels were independently associated with reduced FEV1 (β = −0.330, P = 0.021). These associations were more pronounced among adults aged ≥60 years and individuals with a BMI ≤ 23 kg/m². Conclusion Thyroid autoimmunity, as reflected by elevated TPOAb levels, was associated with a decline in pulmonary function among euthyroid individuals, independent of thyroid hormone levels. Our results support the clinical utility of TPOAb status as an early marker for detecting subclinical pulmonary vulnerability, particularly in older adults and those with a lower BMI.